ARTIFICIAL INTELLIGENCE IN LANGUAGE LEARNING: MICROSOFT READING PROGRESS AND ITS EFFECT ON PRONUNCIATION - Arta Wahyu; Riny Jefri; Lely Novia (Bahasa Inggris Program Sarjana Terapan, Universitas Negeri Makassar, 2026)
This study aims to evaluate the impact of Microsoft Reading Progress on students’ pronunciation skills in English language learning and identify the challenges faced by students in using the tool’s features. This study used a qualitative method involving pronunciation tests before and after using Microsoft Reading Progress, as well as conducting direct interviews. Microsoft Reading Progress, an AI-based tool integrated into Microsoft Teams, provides real-time feedback to students on their pronunciation. The results showed that Microsoft Reading Progress significantly improved students’ pronunciation accuracy and confidence in speaking English. However, there were some limitations in the accuracy of pronunciation error detection and other technical challenges, such as false positives and undetected accent variations. In addition, students faced difficulties in navigating the user interface and understanding the feedback provided. This study suggests the need for more systematic integration of Microsoft Reading Progress into the curriculum, training for educators and students, and ongoing evaluation to optimize the use of the tool. With further refinement, Microsoft Reading Progress has great potential to be an effective tool in improving students’ English pronunciation skills.